Screening for atrial fibrillation in primary care - Taggar, Jaspal (2017)
Background Screening for atrial fibrillation (AF) has been recommended but is yet to be implemented in clinical practice. However, the most effective approaches for screening are not known and it is unclear if screening could feasibly be implemented in primary care.